PENERAPAN PRINSIP HAK ASASI MANUSIA DALAM PEMBERIAN REMISI SEBAGAI HAK WARGA BINAAN PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN BERDASARKAN SISTEM PENILAIAN PEMBINAAN NARAPIDANA - Makmur (Universitas Tadulako, 2024)
The problem of this research is how to apply the principles of human rights in granting remission as a right for inmates based on the assessment system for inmate development, and what are the obstacles to inmate development from a human rights perspective in the Class IIB Tolitoli Penitentiary, using normative-empirical research methods. Based on the research results, the right to remission is also a form of respect and appreciation for the dignity and worth of prisoners who have done good through coaching so that they understand human values as the basis of human rights. Remission is in line with the International Covenant on Civil and Political Rights, the Body of Principles for the Protection of Persons Under Any Form of Detention or Imprisonment, Standard Minimum Rules for the Treatment of Prisoners as a form of human rights protection prisoners to foster prisoners. The implementation of prisoners' rights, especially remission in the Tolitoli Class IIB prison, has gone quite well. All prisoners' rights contained in Law no. 22 of 2022 concerning Corrections and human rights that cannot be reduced (non-derogable rights), so that the state has regulated, fulfilled and protected the rights of prisoners relating to the granting of Remissions such as Remissions and Barriers to the development of prisoners from a human rights perspective at the Class IIB Tolitoli Penitentiary , especially limited facilities and infrastructure, limited religious formation and skills, this is due to limited staff and more emphasis on aspects of security and order, but prisoners' rights remain a priority as a form of protection and fulfillment of prisoners' human rights.